2013
DOI: 10.4276/030802213x13861576675286
|View full text |Cite
|
Sign up to set email alerts
|

Motor Abilities and Coping in Children with and without Developmental Coordination Disorder

Abstract: Introduction: This study was conducted in order to identify differences in motor abilities and coping in children with and without developmental coordination disorder. The study also discusses the relationship between coping and motor abilities. Method: A cross-sectional design with two independent groups was chosen to identify the differences. The Movement Assessment Battery for Children — second edition (Henderson et al 2007) was used to assess motor skills. Coping was evaluated with the Coping Inventory o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
6
0
2
Order By: Relevance
“…Ruckser-Scherb, Roth [107] emphasised that a key aspect of occupational adaptation was the learning that occurs through doing and participating in occupations. When occupational difficulties are encountered, individuals have to use problem solving strategies to facilitate occupational performance.…”
Section: Mastery and Competencementioning
confidence: 99%
See 1 more Smart Citation
“…Ruckser-Scherb, Roth [107] emphasised that a key aspect of occupational adaptation was the learning that occurs through doing and participating in occupations. When occupational difficulties are encountered, individuals have to use problem solving strategies to facilitate occupational performance.…”
Section: Mastery and Competencementioning
confidence: 99%
“…For example, Lexell, Iwarsson [32] described occupational adaptation as an ongoing, dynamic process requiring balancing of identity and competence. The ongoing learning that occurs as part of the occupational adaptation process has also been outlined [107,111]. Several authors, including Ruckser-Scherb, Roth [107], identified that if a response to occupational challenge is adaptive, resulting in success, it is remembered for future use, so enhancing the individual's coping skills.…”
Section: A Life-long Cumulative Processmentioning
confidence: 99%
“…Emotional problems experienced by adolescents with DCD often manifest through anger, frustration, unhappiness, distress, depression and low self-esteem (Smyth and Anderson, 2000). A study by Ruckser-Scherb et al. (2013) adds to these findings by highlighting that there is a relationship between motor coordination difficulties and coping skills.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Emotional problems experienced by adolescents with DCD often manifest through anger, frustration, unhappiness, distress, depression and low self-esteem (Smyth and Anderson, 2000). A study by Ruckser-Scherb et al (2013) adds to these findings by highlighting that there is a relationship between motor coordination difficulties and coping skills. The sample size in this study was small, but the results were significant and supported the fact that children with DCD have more problems 'coping with self' and are not always able to fulfil their personal needs; they also experience difficulty 'coping with environment', being less likely to succeed in adapting to the requirements of others and their surroundings.…”
Section: Social-emotional Difficultiesmentioning
confidence: 99%
See 1 more Smart Citation